Impact of implementing hourly rounding on improving patient satisfaction: A literature review - Lency Karnovty Maria; Blacius Dedi (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Nursing rounds are an implementation of Relationship Based Care. Implementation of nursing rounds allows nurses to have reciprocal relationships with patients and families on a regular and systematic basis. Periodic rounds have been used throughout the world in nursing care to anticipate patient needs while utilizing evidence-based interventions. Purpose: To determine the effectiveness and impact of implementing hourly rounding on improving patient satisfaction Method: A literature review design. The databases used include Google Scholar, Pubmed, and Semantic Scholar. English keywords employed are "hourly rounding", "nursing rounds", and "patient satisfaction". Articles were included if they involved nurses in hospitals or health profession students, with no limit on sample size, and encompassed experimental, quantitative, and qualitative research. Only full-text articles in Indonesian or English published in the last 5 years (2019-2023) were considered. Results: The analysis identified two main topics: the effectiveness of implementing periodic nurse rounds and Nursing Rounds Implementation Management. Overall, the implementing periodic nurse rounds has been shown to meet patient care needs, ensure patient safety, reduce the incidence of patient falls, decubitus ulcers, and medication errors. Conclusion: The implementation of regular nurse rounds every two hours has been proven to increase nurse caring behavior and patient satisfaction. However, the effectiveness of its implementation is influenced by the nurse's ability to manage time.